Occupational Therapy Treatment to Improve Upper Extremity Function in Individuals with Early Systemic Sclerosis: A Pilot Study - Murphy, Susan L. (Arthritis Care Res (Hoboken), 2018)
OBJECTIVE: To determine feasibility and preliminary effects of an occupational therapy treatment to improve upper extremity (UE) function in patients with early systemic sclerosis (SSc) who have UE contractures. METHODS: A one-arm pilot clinical rehabilitation trial was conducted at a university health system. Participants with SSc and > 1 UE contracture (n = 21) participated in a total of 8 weekly in-person occupational therapy sessions. The therapy consisted of thermal modalities, tissue mobilization, and UE mobility. Between sessions, participants were instructed to complete UE home exercises. Feasibility was measured by percent enrollment and session attendance and duration. The primary outcome measure was the QuickDASH, secondary and exploratory outcomes included PROMIS physical function, objective UE measures, and skin thickening. Linear mixed models were performed to determine treatment effects on primary and secondary outcomes. RESULTS: Fifty percent (24/48) of potentially eligible participants were interested. Of those, 88% (21/24) enrolled; and nineteen out of 21 (91%) completed all sessions. The mean (SD) age was 47.9 years (+ 16.1); 100% had diffuse SSc, and mean disease duration was 3.1 years. At 8 weeks, participants reported statistically significant improvement on QuickDASH and PROMIS physical function measures (p =.0012 and p = .004). Forty-seven and 53% percent of the sample achieved improvements that exceeded minimally important differences. CONCLUSION: In-person treatment sessions were feasible for individuals with SSc and demonstrated statistically significant and clinically meaningful improvements on UE and physical function. Future studies need to examine effects against a control condition and examine durability of treatment effects.